(untitled) (Homiletic, 2020)
Many contemporary preachers and homileticians address what they believe to be a “crisis” of preaching. Without denying these claims, this essay offers theological and homiletical insights from the young Karl Barth on what he believed to be a more fundamental and pervasive homiletical crisis subsuming all others. Just what this crisis was for Barth becomes clearer when we look to the sociopolitical commitments of two of Barth’s pastoral mentors: Friedrich Naumann and Christoph Blumhardt. Drawing from his theologico-political discernment leading up to the Great War, Barth offers us ways to challenge unjust and oppressive policies and systems through our preaching ministries today.